Analysis Of the Effect of Internal Performance on Bank Profitability - Tri Basuki, Agus; Rahman, Arif (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the effect of CAR, LDR, NPL, BOPO, and Bank Size. This study uses quantitative methods and panel data regression models to investigate how internal factors or bank ratios affect the profitability of KBMI 3 and 4 banks in Indonesia. The research sample consisted of 8 KBMI banks 3 and 4 using Purposive Sampling covering the 2015-2022 period. The estimation method in the selected panel data is the Fixed Effect Model approach. The results of this study show that the profitability of Bank KBMI 3 and 4, as measured by ROA, partially LDR variables have a significant positive influence, BOPO and Asset Size have a significant negative influence, CAR and NPL do not have a significant and negative effect, while simultaneously have a significant influence. The findings of this study provide empirical evidence regarding the effect of financial ratio variables or internal bank factors on the profitability of Bank KBMI 3 and 4, which in turn can be useful for policy makers, academics, and investors.